2011
DOI: 10.1002/ceat.201100192
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Technologies for the Remediation of Diesel Fuel Polluted Soil

Abstract: Diesel fuel may be released into soil due to anthropogenic activities, such as accidental spills or leaks in underground storage tanks or pipelines. Since diesel fuel is mainly composed of hydrophobic organic compounds, it has low water solubility. Therefore, treating contaminated areas with conventional techniques is difficult. In this study, electrokinetic treatment of soil contaminated with diesel fuel was carried out. Two different hybrid approaches to pollutant removal were tested. A surfactant was used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 31 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…In the search for effective and economically competitive dieselpolluted soil remediation strategies, several options have been proposed including chemical-physical or biologic treatments (Do et al, 2009;Dong et al, 2013;Fernández et al, 2011;Khalladi et al, 2009;Mena et al, 2014;Pazos et al, 2011;Tomei et al, 2013;Tsai et al, 2010). However, these treatments may be ineffective, too expensive or lengthy (Chien, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the search for effective and economically competitive dieselpolluted soil remediation strategies, several options have been proposed including chemical-physical or biologic treatments (Do et al, 2009;Dong et al, 2013;Fernández et al, 2011;Khalladi et al, 2009;Mena et al, 2014;Pazos et al, 2011;Tomei et al, 2013;Tsai et al, 2010). However, these treatments may be ineffective, too expensive or lengthy (Chien, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among hydrocarbons, petroleum-derived diesel is composed of approximately 75% saturated hydrocarbons (primarily paraffins), and 25% aromatic hydrocarbons (including naphthalenes and alkylbenzenes), and it represents a permanent source of soil pollution (Pazos et al, 2011). In the search for effective and economically competitive dieselpolluted soil remediation strategies, several options have been proposed including chemical-physical or biologic treatments (Do et al, 2009;Dong et al, 2013;Fernández et al, 2011;Khalladi et al, 2009;Mena et al, 2014;Pazos et al, 2011;Tomei et al, 2013;Tsai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxyl radicals generated in the Fenton reaction are strong and relatively unspecific oxidants that react with most organic contaminants by abstracting hydrogen atoms or by adding to double bonds [29]. Pazos et al [30] studied the removal of diesel fuel from contaminated soil using 10% H 2 O 2 as processing fluid. Approximately 87% diesel removal was achieved after 30 days of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…and Triton X-100 are often used because of their low toxicity, a good hydrocarbon compounds solvent, relatively low CMC, the potential is absorbed into low soil particles and is easily degraded by microorganism (Cheng et al, 2017;Pazos et al, 2011). In the recent study conducted by Wan et al (2010), Triton X-100 (TX100) integrated with permeable reactive barrier is able to remediate 64.2% of hexachlorobenzene (HCB) in polluted soil.…”
Section: Surface Charge Of Surfactantmentioning
confidence: 99%
“…Xu et al (2010) reported that an electrolyte circulation less than 800 ml/h cannot control the pH fluctuations well. The buffer solution can also be used as a control pH although it is not effectively used for long periods of time (Kim et al, 2010;Park et al, 2007;Pazos et al, 2011).…”
Section: Electrokinetic System and Configurationmentioning
confidence: 99%